The Impact of Academic Supervision and Work Discipline on Teacher’s Performance - Marzuki, Muhammad (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
The purpose of this study is to assess, both partially and concurrently, the influence of the principal's academic supervision and work discipline on the performance of teachers at SD Negeri 25 Talang Ubi. This is a quantitative study using factors such as principal supervision, work discipline, and teacher performance. All ten instructors of SD Negeri 25 Talang Ubi were included in the sample. The distribution of a questionnaire with four Likert scales, which has been verified for validity and reliability, was utilized as the study instrument. The data analysis approach employs basic and multivariate regression. Based on the findings, it is possible to infer that the principal's academic supervision has a favorable and significant impact on teacher performance. Academic supervision and work discipline provided by the principal have a favorable and significant impact on teacher performance. Based on the coefficient of determination of the principal's academic supervision variable and work discipline, it made a significant contribution to the teacher's performance; the remainder was impacted by other variables not included in the study variables. This study was carried out to aid in the improvement of teacher performance by focusing on the implementation of academic monitoring and the use of maximal teacher discipline.